Transforming the Education System Amidst Technological Developments by Utilizing E-Learning in the Digital Era - Rayhan Aria Shiddiq (Manajia: Journal of Education and Management, 2025)
E-learning, as a technology-based educational innovation, offers an effective solution for distance learning by utilizing Learning Management Systems (LMS). This article discusses the development of e-learning from computer-based systems to more interactive web-based applications. E-learning increases flexibility, accessibility, and student engagement. However, challenges such as technology gaps and resistance to change need to be addressed for e-learning to be effectively implemented at various levels of education. The implementation of e-learning can be an alternative to improve the quality of education with a more modern and adaptive approach.